FRI0421 Dysregulated MIR-125 promotes joint angiogenesis in PSA through altered bioenergetics. (15th June 2017) - Wade, S; Ohnesorge, N; Biniecka, M; Merrigan, S; McGarry, T; Canavan, M; Veale, DJ; Kennedy, B; Fearon, U
Abstract : Background: Psoriatic arthritis (PsA) is characterised by an early vascular phase which is essential in perpetuating pannus growth, immune responses and disease progression. Recently, numerous studies have highlighted the emerging importance of endothelial cell metabolism in controlling angiogenesis. Herein, we propose microRNA, miR-125, modulates EC bioenergetics and orchestrates joint angiogenesis as characterised using ex-vivo and in-vitro tissue/cell assays and a novel in-vivo zebrafish model. Objectives: To examine the relationship between miR-125, angiogenesis and cellular metabolism in the PsA synovium. Methods: Primary PsA synovial fibroblasts (PsA FLS) and microvascular endothelial cells (HMVEC) were transfected with anti-miR-125a. Angiogenic mechanisms were quantified using tube formation assays, invasion by Transwell Matrigel chambers, migration by wound repair and metabolic gene expression by RT-PCR. Real-time analysis of extracellular acidification rates (ECAR) and oxygen consumption rates (OCR) of anti-125 treated HMVEC was assessed using the XF-24 Flux Analyzer (Seahorse Bioscience). To determine if altered metabolism is observed ex vivo, glycolysis/oxidative phosphorylation markers (GAPDH/PKM2/GLUT1/ATP), and angiogenic factors (FactorVIII/VEGF/ANG2) were quantified by immunohistology. MiRNA levels were quantified in synovial tissue (ST) and PBMC by RT-PCR and compared to clinical marker and immunohistochemical analysis. The angiogenic effects of miR-125 were assessed in vivo using GFP-tagged zebrafish embryos treated with anti-125 morpholinos, or vitamin D3 analog, calcitrol, to monitor vascular development. Results: An increase in tube formation, cellular invasion and/or migration mechanisms (p<0.05) were demonstrated in anti-miR-125a transfected HMVEC and FLS supernatant. Inhibition of miR-125 significantly decreased basal, maximal and spare respiratory capacity (P<0.009) with a concurrent decrease in ATP synthesis (P<0.008). Increased glycolysis was further confirmed by the observed elevation of glycolytic genes: HK2, GSK3A, PDK1, HP6G (ns) and 3PO target and stimulator of glycolysis, PFKFB3 (P<0.05). In vivo synovial expression of miR-125 was significantly decreased in PsA versus OA synovial tissue and was associated with increased PsA macroscopic and microscopic vascularity. This was paralleled by a significant increase in the vascular expression of glycolytic markers, PKM2, GLUT1 and ATP5B in PsA compared to OA synovium. Finally, anti-125 morpholinos treated Zebrafish displayed increased vascular sprouting. In contrast, Calcitriol significantly reduced vascular development and increased the expression of miR-125, promoting miR-125 as a potential mechanism for orchestrating angiogenic development in vivo and in response to pharmaceutical agents Conclusions: Our data demonstrates decreased expression of miR-125 in PsA synovium and in-vivo models was strongly associated pro-angiogenic mechanisms. Elevated glycolysis following miR-125 inhibition may enables endothelial cells to meet the increased energy and biosynthetic demands for new vessel formation. Correcting these deficiencies and their resulting metabolic shift, either by conventional pharmacological or as novel drug targets, may provide therapeutic benefit, especially in early disease. Disclosure of Interest: None declared